Análisis del cumplimiento del pronóstico deportivo en juegos nacionales categoría menores, de los deportistas de halterofilia, de la provincia de Zamora Chinchipe durante el periodo 2015-2019 - Beltrán Valverde, Melisa Eufemia (2021)
The present investigative work has as title: "ANALYSIS OF THE COMPLIANCE OF THE SPORTS FORECAST IN NATIONAL GAMES MINOR CATEGORY, OF THE HALTEROFILIA SPORTSMEN, OF THE PROVINCE OF ZAMORA CHINCHIPE DURING THE PERIOD 2015-2019", whose problem is the following: Was the sports forecast fulfilled in National Games underage category, of weightlifting athletes, from the province of Zamora Chinchipe during the period 2015-2019? In order to solve the problem, the general objective was: To analyze the fulfillment of the sports forecast in the National Games of weightlifting athletes of the province of Zamora Chinchipe during the period 2015- 2019, focusing scientifically on the dependent variables, which are the forecasts issued and the independent one, which are the National Games of Minors. In this research the mixed approach was used. Its design is non-experimental and transactional or transversal descriptive research. Bibliographic, expert consultation, deductive, inductive, historical- logical, analytical, descriptive and statistical methods were applied. Techniques used: interview, survey, and document analysis. Instruments: interview guide, questionnaire of questions and document analysis guide. With the predisposition of these instruments, it is concluded that the essential factors that weightlifting coaches of Provincial Sports Federation of Zamora Chinchipe consider to issue forecasts for National Junior Games of each year of this research (2015-2019); are: the economic, medical, psychological, social, training and somatotype factor of the athlete, giving as results that Provincial Sports Federation of Zamora Chinchipe has obtained good and bad results based on the forecasts during this period.